1996
DOI: 10.1093/ajcp/106.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Barrett Esophagus With Dysplasia:Flow Cytometric DNA Analysis of Routine, Paraffin-Embedded Mucosal Biopsies

Abstract: Flow cytometric DNA ploidy analysis has been reported to be more objective and sensitive than morphologic evaluation as a surveillance method in patients with Barrett esophagus (BE) for the development and progression of precancerous lesions. Such analyses are typically performed using fresh samples that require a separate or "jumbo" biopsy, are prone to false DNA aneuploidy if not promptly processed, and do not allow for retrospective studies. The feasibility of performing flow cytometric DNA analysis on para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 9 publications
1
15
0
4
Order By: Relevance
“…Montgomery et al reported that DNA aneuploidy was present in 77% of HGD,29 whereas only 32% of HGD showed DNA content abnormality in another study 22. In our cohort, abnormal flow cytometric results were identified in 95% of HGD, 21.1% of LGD, 9.5% of IND and no sample without dysplasia.…”
Section: Discussionmentioning
confidence: 41%
“…Montgomery et al reported that DNA aneuploidy was present in 77% of HGD,29 whereas only 32% of HGD showed DNA content abnormality in another study 22. In our cohort, abnormal flow cytometric results were identified in 95% of HGD, 21.1% of LGD, 9.5% of IND and no sample without dysplasia.…”
Section: Discussionmentioning
confidence: 41%
“…The evolution of clones that we report here is also consistent with neoplasia, and recognition of BE as a benign neoplasm may improve our understanding of the basis for its precancerous potential. The study of evolution requires measurement of changes in allele frequencies, and we did not assess the relationship between genotypes and dysplastic phenotypes because the two were generated on different samples that could not be directly compared quantitatively, although the relationships among p16, p53, and cytometric abnormalities and dysplasia have been published previously by us and others (2,17,18,25,69,(82)(83)(84)(85)(86).…”
Section: Markermentioning
confidence: 99%
“…[35][36][37] Moreover, abnormal DNA content shows a correlation with the histologic diagnosis of dysplasia and carcinoma. 38,39 Flow cytometry also detects a subset of patients whose biopsy samples are histologically indefinite or negative for dysplasia and carcinoma but who have DNA content abnormalities similar to those otherwise seen only in dysplasia and carcinoma. 37,40 Therefore, this technique (in combination with histology) may be useful in screening patients with BE for early signs of malignant change.…”
Section: Dna Content/aneuploidymentioning
confidence: 99%